2018
DOI: 10.1186/s12911-018-0701-z
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to exchanging healthcare information in inter-municipal healthcare services: a qualitative case study

Abstract: BackgroundIn recent years, inter-municipal cooperation in healthcare services has been an important measure implemented to meet future demographic changes in western countries. This entails an increased focus on communication and information sharing across organisational borders. Technology enables efficient and effective solutions to enhance such cooperation. However, the systems in the healthcare sector tend not to communicate with one another. There is a lack of literature focusing on communication and info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 37 publications
0
7
1
Order By: Relevance
“…Threat appraisal, which included intrinsic rewards, extrinsic rewards, severity, and vulnerability as subfactors, was found to have no effect on the nurses' HIS intentions and behavior. The results of the studies by Kim et al [33] and Holen et al [20], who reported more beneficial HIS intentions and behavior effects, are in contrast to the results of this study. This suggests that nurses are aware of the importance of HIS behavior and the associated risks to patients, and do not simply seek intrinsic rewards such as satisfaction and achievement when exhibiting HIS behavior.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Threat appraisal, which included intrinsic rewards, extrinsic rewards, severity, and vulnerability as subfactors, was found to have no effect on the nurses' HIS intentions and behavior. The results of the studies by Kim et al [33] and Holen et al [20], who reported more beneficial HIS intentions and behavior effects, are in contrast to the results of this study. This suggests that nurses are aware of the importance of HIS behavior and the associated risks to patients, and do not simply seek intrinsic rewards such as satisfaction and achievement when exhibiting HIS behavior.…”
Section: Discussioncontrasting
confidence: 99%
“…Additionally, we considered the intention to be the adoption of actions to protect oneself from threats [17]. Subfactors related to threat appraisal include intrinsic rewards, extrinsic rewards, severity, and vulnerability, according to the results of prior studies [5,12,[18][19][20][21][22][23][24], leading to the following hypothesis: Hypothesis 1 (H1). The threat appraisal of HIS by nurses will affect their intentions.…”
Section: Anticipated Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the years, though these standards have supported the field's progress, they also contribute to the unintended consequence of creating professional silos and biases that impact public health. Examples include fragmented healthcare delivery ( 70 ), barriers to information sharing ( 71 ), and the fallacy of “Expert Immunity,” or the incorrect belief that experts are impartial or immune to biases due to their expertise ( 72 ).…”
Section: Expanding Public Health Through Designmentioning
confidence: 99%
“…Other scholars have studied the implementation of technology in healthcare settings [ 17 , 24 26 ], and the NPT has been applied for structuring the analysis and results of these studies [ 13 , 14 , 23 , 27 ]. Collaboration between public healthcare services using technology has also been previously studied [ 28 31 ], showing the importance of achieving understanding, commitment and engagement towards an intervention to succeed [ 13 , 14 , 23 , 27 ]. What differentiates our study is that the implementation process involved employees from the public and civil sectors, that is, employees in municipal healthcare units and volunteer centres, providing insights into the implementation of technology that can help different organisations collaborate on the coordination of volunteers.…”
Section: Discussionmentioning
confidence: 99%